PENGARUH GOOD CORPORATE GOVERNANCE, KOMPOSISI ASSET TETAP, KESEMPATAN TUMBUH DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Yustinus Adhi Setiawan, 13.05.62.0012; Kartika, Andi (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of good corporate governance, asset mix, the chance to grow and the size of the company to the companys performance in the companys corporate governance program preception CGPI index listed on the Indonesia Stock Exchange in 2011-2014. The population used in this study is a company that follows the corporate governance program preception CGPI index listed on the Indonesia Stock Exchange in 2011-2014. The sample in this study were 60 observation data. The sampling technique used purposive sampling. The criteria for the sample in this study is the companies included in the "Most Trusted Company Based On Corporate Governance Preception Index" published by IICG since 2011 until 2014; Companies listed on the Indonesia Stock Exchange; had complete data for the study variables. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Good corporate governance, Composition of fixed assets, The opportunity to grow no significant effect on ROE. Size companies positive effect on ROE. The higher the size of the company, the return on equity will increase.Keywords: Good Corporate Governance, Asset Mix, The Chance to Grow, The Size of The Company and The Companys PerformanceÂ